1990
DOI: 10.1111/j.1095-8649.1990.tb05870.x
|View full text |Cite
|
Sign up to set email alerts
|

The status of the barbel, Barbus barbus (L.) (Teleostei, Cyprinidae), in the United Kingdom

Abstract: The barbel was originally a fish with a relatively restricted range in the British Isles. However, despite the general environmental degradation of many British rivers, and in contrast with some native freshwater fishes, the barbel is now more widely distributed than it was a century ago. It may even be more abundant numerically.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
54
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(56 citation statements)
references
References 4 publications
1
54
1
Order By: Relevance
“…River regulation has been identified as a major threat to barbel populations (Pilcher et al, 2004), with compounding adverse effects of elevated nutrient levels on the species' morphology (Tyler and Everett, 1993), physiology (Peňáz et al, 2005) and migratory behaviour (Lucas and Frear, 1997;Vilizzi et al, 2006). This contrasts with earlier, more optimistic assessments that suggested that B. barbus numbers were on the increase (Wheeler and Jordan, 1990). Thus, information on population size structure and growth is needed for rivers where B. barbus stocks are thought to be in decline so as to inform environmental managers in the formulation of habitat enhancement/rehabilitation and re-stocking strategies that aim to conserve the populations and increase the related angling amenity Pegg and Britton, 2011).…”
Section: Introductioncontrasting
confidence: 43%
See 1 more Smart Citation
“…River regulation has been identified as a major threat to barbel populations (Pilcher et al, 2004), with compounding adverse effects of elevated nutrient levels on the species' morphology (Tyler and Everett, 1993), physiology (Peňáz et al, 2005) and migratory behaviour (Lucas and Frear, 1997;Vilizzi et al, 2006). This contrasts with earlier, more optimistic assessments that suggested that B. barbus numbers were on the increase (Wheeler and Jordan, 1990). Thus, information on population size structure and growth is needed for rivers where B. barbus stocks are thought to be in decline so as to inform environmental managers in the formulation of habitat enhancement/rehabilitation and re-stocking strategies that aim to conserve the populations and increase the related angling amenity Pegg and Britton, 2011).…”
Section: Introductioncontrasting
confidence: 43%
“…Increasingly threatened within its native range (Peňáz et al, 2003), the IUCN status of B. barbus therefore carries the caveat of being "locally threatened by water pollution and river regulation". In the UK, where B. barbus is native to eastern rivers between Yorkshire and the Thames (Wheeler and Jordan, 1990), declining population densities have been reported for some of the more urbanised rivers, including the River Lee, Hertfordshire (Pilcher and Copp, 1997;Watkins et al, 1997). River regulation has been identified as a major threat to barbel populations (Pilcher et al, 2004), with compounding adverse effects of elevated nutrient levels on the species' morphology (Tyler and Everett, 1993), physiology (Peňáz et al, 2005) and migratory behaviour (Lucas and Frear, 1997;Vilizzi et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…A strong example is the European barbel Barbus barbus where, in Britain, this cyprinid fish is only indigenous to eastern flowing rivers, but has now been introduced for angling into numerous rivers in their nonindigenous range (Wheeler and Jordan, 1990;Antognazza et al, 2016). In the River Severn, western England, 509 adult fish were introduced in 1956 for fishery enhancement (Wheeler and Jordan, 1990).…”
mentioning
confidence: 99%
“…A strong example is the European barbel Barbus barbus where, in Britain, this cyprinid fish is only indigenous to eastern flowing rivers, but has now been introduced for angling into numerous rivers in their nonindigenous range (Wheeler and Jordan, 1990;Antognazza et al, 2016). In the River Severn, western England, 509 adult fish were introduced in 1956 for fishery enhancement (Wheeler and Jordan, 1990). These fish established and dispersed throughout the middle and lower river, with reports in the 1970s of their capture by anglers in the River Teme, a major tributary of the Severn (Hunt and Jones, 1975;Wheeler and Jordan, 1990;Antognazza et al, 2016;Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation